Intraguild predation influences oviposition behavior of blow flies (Diptera: Calliphoridae) - Galindo, Luciane A. [UNESP]; Moral, Rafael A.; Moretti, Thiago C.; Godoy, Wesley A. C.; Demétrio, Clarice G. B. (Springer Nature, 2016)
The objective of the present study was to determine whether blow flies (Diptera: Calliphoridae) are able to identify larvae of an intraguild predator species in the substrate and avoid laying eggs there. Blow flies oviposited in traps with different treatments: substrate only and substrate with larvae of Chrysomya albiceps (Wiedemann, 1819), Chrysomya megacephala (Fabricius, 1794), or Chrysomya putoria (Wiedemann, 1830). Ch. megacephala, Ch. putoria, and Lucilia eximia (Wiedemann, 1819) avoided laying eggs in the trap containing Ch. albiceps larvae. Cochliomyia macellaria (Fabricius, 1775) did not oviposit differently in each substrate but had overall low abundance. The prevalence of species on corpses may be influenced by the ability of the species to detect the presence of other species, mainly predators. In this sense, intraguild predation may result in misinterpretations of a crime scene and should be considered when assessing the minimum postmortem interval.
Keywords: Avoidance behavior; Blow fly ecology; Cannibalism; Chrysomya albiceps; Chrysomya megacephala; Chrysomya putoria